Control of transients in drinking water networks. (February 2022) - Martin, A.; Delgado-Aguiñaga, J.A.; Puig, V.
Abstract: In this paper, we propose a model-based design approach for the effective control of a drinking water system to reduce the effect of hydraulic transients and meet pressure service requirements regardless of the demand pattern. We model pressure drops along a drinking water system according to a finite-difference approximation of the classical water hammer equations (WHE), and then apply the proposed control strategy to a section of the distribution network located in the metropolitan city of Barcelona. First, a model of the case study network is derived to reproduce the sustained pressure oscillations measured in the real system. Second, a decentralized control scheme composed of an optimal proportional–integrative (PI) controller with anti-windup and a series of model predictive controllers are designed. This control architecture allows to optimally regulate the service pressure while satisfying safety constraints, regardless of water demand fluctuations. Numerical simulations are used to assess the effectiveness of the proposed solution.